Comparison of finasteride versus spironolactone in the treatment of idiopathic hirsutism - (:unkn) unknown (My University, 1997)
OBJECTIVE: To compare the efficacy of finasteride and spironolactone in the treatment of idiopathic hirsutism. DESIGN: Prospective, randomized, single-blind study. SETTING: A tertiary hirsutism clinic. PATIENT(S): Forty women with idiopathic hirsutism were selected. INTERVENTION(S): Patients were assigned randomly to receive either 5 mg of finasteride or 100 mg of spironolactone for 9 months. MAIN OUTCOME MEASURE(S): Hirsutism scores were measured according to the Ferriman-Gallwey scoring system, and side effects were monitored for 9 months of treatment. Blood samples were taken at each visit for assessment of endocrine, biochemical, and hematologic parameters. RESULT(S): Hirsutism scores were decreased significantly in both groups at the end of 9 months. The mean percent change (+/- SD) in hirsutism scores in the finasteride and spironolactone groups was as follows: 5.91% +/- 7.18% and 20.60% +/- 12.59% at 3 months, 10.61% +/- 12.18% and 32.57% +/- 15.68% at 6 months, and 15.15% +/- 15.38% and 42.36% +/- 12.31% at 9 months, respectively. There was a significantly better response with spironolactone treatment at the end of 9 months. Eleven (55%) of 20 patients in the spironolactone group experienced side effects. However, none of them stopped treatment because of side effects. CONCLUSION(S): The present data suggest that both finasteride and spironolactone are effective in the treatment of idiopathic hirsutism. However, it appears that the spironolactone group responded significantly better.
Keywords: Adult; Female; Humans; Treatment Outcome; Prospective Studies; Drug Administration Schedule; Single-Blind Method; Enzyme Inhibitors; Hirsutism; Mineralocorticoid Receptor Antagonists; Spironolactone; Finasteride; Gonadal Steroid Hormones